Interest Rate Transmission to Commercial Credit Rates in Austria - Johann Burgstaller (Johannes Kepler University of Linz, Department of Economics, 2003)
The transmission process from policy-controlled interest rates to bank lending rates deserves reconsideration owing to the implementation of the European Monetary Union (EMU) in 1999. Additional attention to the subject in Austria is due to several large banks which, in 2002, have been charged for not passing on interest rate decreases to their customers. I examine dynamic responses of commercial credit rates to changes in key policy rates and money market rates. Using Austrian data from 1995 to 2002, I show that strength and speed of interest rate transmission depend on whether rates go up or down. With the EMU, asymmetry in interest rate transmission partly declined. The speed of transmission and the relative importance of policy and money market rates for commercial credit rates also were affected.
Keywords: E43; E52; G21; G30; 330; Monetary policy transmission; interest rate pass-through; bank lending rates for commercial credit; European Monetary Union; impulse-response analysis; Transmissionsmechanismus; Geldpolitik; Europäische Wirtschafts- und Währungsunion; Österreich